Хоккей с шайбой - Тарасов Анатолий Владимирович (В помощь инструктору-общественнику, 1956)
Экземпляры: КХ (20210615) / Инвентарный номер: 205723 / Сис.шифр: 796.3 / Авт.знак: Т 19 / ГРНТИ: 77.29.64 / ББК: 75.579.5